EVALUASI PENERAPAN PROGRAM 5R (RINGKAS, RAPI, RESIK, RAWAT, RAJIN) DI BATCHING PLANT HALIM PT. X TAHUN 2022 - Muhammad Salman (2022)
5S Program (Sort, Set, Shine, Standardize, Sustain) is a program that aims to assist companies in realizing effectiveness, productivity, and work efficiency and safety at the company. The implementation of this 5S program can improve product quality by managing the environment in the company so that it is clean and neat and can minimize and prevent the occurrence of work accidents and occupational diseases (PAK) in the company. The implementation of the 5S program is mostly applied to manufacturing companies, one of which is PT. X. PT. X has implemented the 5S program since the establishment of the company, but in 2018 a review was carried out again related to the 5S program procedure at PT. X to increase the effectiveness of the 5S program in the company. This study aims to evaluate the application of 5S program (Sort, Set, Shine, Standardize, Sustain) at PT. X year 2022. This study used a descriptive study design with qualitative research methods through in-depth interviews with selected informants and observation using a check form to see the application of the 5S program. The results showed that the implementation of the 5S program at PT.X has been implemented in accordance with the 5S program guidelines at PT. X, but there is still a need for increased supervision and awareness of employees. Advice for the company is to conduct regular supervision in the implementation of the 5S program and provide training on the importance of implementing the 5S program in the company.